Simultaneous Determination of Cortisol and Cortisone from Human Serum by Liquid Chromatography-Tandem Mass Spectrometry - Sanghoo Lee; Hwan-Sub Lim; Hye-Jin Shin; Seol-A Kim; Jimyeong Park; Hyun-Chul Kim; Hyogyeong Kim; Hyung Joo Kim; Yun-Tae Kim; Kyoung-Ryul Lee; Young-Jin Kim (Journal of Analytical Methods in Chemistry)
A fast, sensitive, and selective liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was validated and then the levels of cortisol and cortisone from sera of healthy adults were determined by the LC-MS/MS method. One hundred μL of serum sample was directly extracted by adding 2 mL ethyl acetate, followed by chromatographic separation on a C18 column with a mobile phase consisting of 5 mM ammonium acetate and methanol (25 : 75, v/v). The precision, accuracy, and average recovery of the method were 1.5–5.3%, 95.4–102.5%, and 96.4% for cortisol, and 1.9–6.0%, 89.2–98.8%, and 79.9% for cortisone, respectively. The method was linear from 1.0 to 500.0 ng/mL r2=0.999 for cortisol and 2.5 to 100.0 ng/mL r2=0.998 for cortisone. The limits of detection (LOD) and quantification (LOQ) were 0.2 and 1.0 ng/mL for cortisol, and 1.0 and 2.5 ng/mL for cortisone, respectively. The average cortisol concentration (133.9±63.7 ng/mL) of samples collected between 9:00 and 11:00 a.m. was higher approximately 4.4 times than that of cortisone (30.5±10.7 ng/mL) P<0.0001. The average cortisone/cortisol ratio was 0.225. Therefore, the LC-MS/MS method may be useful for the diagnosis of some adrenal diseases and the assessment of 11β-hydroxysteroid dehydrogenase (11β-HSD) activity in clinical laboratories.